Botswana : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper and Statistical Appendix describes the evolution of Botswana's exchange rate regime against the background of the country's main economic developments and trade relations. The paper reviews the main changes that have taken place in Botswana's exchange rate arrangement, and discusses the development of the country's external trade. Indicators of competitiveness are presented, and some conclusions are drawn about the appropriateness of Botswana's exchange rate regime and its role in economic diversification.